2014
DOI: 10.1186/1471-230x-14-58
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of Helicobacter pylori infection in Behcet’s disease

Abstract: BackgroundBehcet’s disease (BD) is a multisystem disease of unknown etiology. There are several clues which may indicate an ethiopathogenesis role for Helicobacter pylori infection in this disease.MethodsIn a case control study in an out patient department, 48 patients with BD were compared to age, sex matched controls regarding presence of H. pylori infection by serology and urea breath test (UBT).ResultsOngoing H. pylori infection was more prevalent among patients with BD using result of UBT with odds ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…BD also frequently involves other organs such as the vascular system, musculoskeletal system, gastrointestinal (GI) tract and central nervous system (CNS). The etiology and pathogenesis of BD is not completely understood but it may be an inflammatory reaction triggered by microbial agents [1][2][3][4][5][6][7][8][9] in a genetically susceptible host. [10][11][12][13][14][15][16][17][18][19] In addition to microbial agents, other environmental factors such as vitamin D deficiency [20][21][22][23][24] are also important.…”
Section: Introductionmentioning
confidence: 99%
“…BD also frequently involves other organs such as the vascular system, musculoskeletal system, gastrointestinal (GI) tract and central nervous system (CNS). The etiology and pathogenesis of BD is not completely understood but it may be an inflammatory reaction triggered by microbial agents [1][2][3][4][5][6][7][8][9] in a genetically susceptible host. [10][11][12][13][14][15][16][17][18][19] In addition to microbial agents, other environmental factors such as vitamin D deficiency [20][21][22][23][24] are also important.…”
Section: Introductionmentioning
confidence: 99%
“…This research identified 91 related references, of which 6 papers met our inclusion criteria . The flowchart that described the process of study selection is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…This research identified 91 related references, of which 6 papers met our inclusion criteria. [13][14][15][16][17][18] The flowchart that described the process of study selection is shown in Figure 1. There were 1119 participants including 449 patients with BS and 670 healthy controls.…”
Section: Basic Characteristicsmentioning
confidence: 99%
“…It has been reported that active H pylori infection, as diagnosed with UBT, was 3.1 times more prevalent among patients with BD than in controls. 88 Moreover, in a small cohort of patients with BD, a significant improvement in the number and size of oral and genital ulcers was observed after H pylori eradication. 89 These findings were confirmed in a recent meta-analysis, reporting that BD patients were more susceptible to H pylori infection, with an OR of 1.39 (95% CI, 1.03-1.87).…”
Section: Autoimmune Diseasesmentioning
confidence: 97%